Nutritional and anti-nutritional compositional analysis of transgenic potatoes with late blight resistance - Moyo, Mukani; Magembe, Eric; Mwaura, Lucy; Byarugaba, Arinaitwe Abel; Barekye, Alex; Nyongesa, Moses; Taracha, Catherine; Ghislain, Marc (Frontiers in Bioengineering and Biotechnology, 2024)
Late blight, caused by the pathogen Phytophthora infestans, is a devastating disease affecting potato production globally, with adverse effects in Africa where limited access to fungicides exacerbates its impact. Outbreaks of late blight lead to reduced yields and substantial economic losses to potato farmers and agricultural systems. The development of resistant potato varieties, tailored to African agroecological conditions, offers a viable solution in mitigating the devastating effects of late blight on potato cultivation. Leading to this study, two consumer-preferred varieties, Victoria and Shangi, with high susceptibility to late blight were targeted for conferring late blight resistance through genetic engineering. This was achieved by inserting R genes from wild relatives of potato displaying resistance to the disease. The intended effect of conferring resistance to the late blight disease has been consistently observed over twenty experimental field trials spanning eight years at three locations in Uganda and Kenya. In this study, we assessed whether the genetic transformation has led to any significant unintended effects on the nutritional and anti-nutritional composition of potato tubers compared to the non-transgenic controls grown under the same agroecological conditions. The compositional assessments were conducted on commercial-size potato tubers harvested from regulatory trials at three locations in Uganda and Kenya. Statistical analysis was conducted using two-way analysis of variance comparing transgenic and non-transgenic samples. Overall, the results showed that the transgenic and nontransgenic samples exhibited similar levels of nutritional and antinutritional components.Variations detected in the levels of the analysed components fell within the expected ranges as documented in existing literature and potato composition databases. Thus, we conclude that there are no biologically significant differences in the nutritional and anti-nutritional composition of transgenic and non-transgenic potato tubers engineered for resistance to late blight.